2014
DOI: 10.1097/ccm.0000000000000498
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Death in the PICU at Five U.S. Teaching Hospitals*

Abstract: Objective To determine the epidemiology of death in pediatric intensive care units (PICUs) at 5 geographically diverse teaching hospitals across the United States. Design, Setting, and Patients In the PICUs of five teaching hospitals across the United States, we prospectively identified 192 consecutive patients who died prior to PICU discharge. Each site enrolled between 24 and 50 patients. Each PICU had similar organizational and staffing structures. Interventions None Measurements and Main Results The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
166
5
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(199 citation statements)
references
References 23 publications
16
166
5
12
Order By: Relevance
“…The incidence of certified BD (N = 103) at the 7 PICUs that participated in the study was 1% of all admissions, which accounted for 13.4% of mortality, similar to the values observed in other international studies 3,9 and in a multicenter study conducted in Argentina that included 16 PICUs and determined that BD accounted for 11% of deaths (52 out of 448).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The incidence of certified BD (N = 103) at the 7 PICUs that participated in the study was 1% of all admissions, which accounted for 13.4% of mortality, similar to the values observed in other international studies 3,9 and in a multicenter study conducted in Argentina that included 16 PICUs and determined that BD accounted for 11% of deaths (52 out of 448).…”
Section: Discussionsupporting
confidence: 62%
“…2 The incidence of BD at the PICU accounts for approximately 16% of deaths. 3,4 The most common cause of BD is trauma. 5 In the field of pediatrics, the need for solid organ donations has increased worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Research from Australia, 4,5,9 the United States, 10,11 and the United Kingdom 1 has found that children most frequently die as a result of withdrawal of life support, whereas studies from Brazil, 3 France, and Eastern and Central Europe 2 identify that most children die in PICUs as a result of failed cardiopulmonary resuscitation. Some have argued that this can be attributed largely to cultural differences related to end-oflife care practices and the social acceptance of the death of a child.…”
mentioning
confidence: 99%
“…2 La incidencia de ME en las UTIP es de alrededor del 16% de las muertes. 3,4 La causa más frecuente son los traumatismos. 5 En el ámbito pediátrico, existe, a nivel mundial, un incremento en la necesidad de donación de órganos sólidos.…”
Section: Introductionunclassified